ANTIBACTERIAL ACTIVITY OF TABERNAEMONTANA DIVARICATA (APOCYNACEAE) SECONDARY METABOLITES CAPPED SILVER AND GOLD NANOPARTICLES - M, Purushothaman; Raj Jp, Preetam; A, KHUSRO; Sg, Panicker (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: To study the antibacterial activity of Tabernaemontana divaricata (Apocynaceae) secondary metabolites capped silver nanoparticles (SNPs) and gold nanoparticles (AuNPs). Methods: In the present investigation, SNPs and AuNPs were synthesized using an aqueous extract of T. divaricata leaves. Leaf aqueous extract was mixed with 1 mM silver nitrate and chloroauric acid for the biosynthesis of nanoparticles, and the same was analyzed using ultraviolet-visible (UV-Vis) spectrophotometer and particle size analyzer. The antibacterial activity of SNPs and AuNPs was determined against various bacterial cultures including laboratory isolates using the agar well diffusion method. Results: The results recorded from UV-Vis spectrum supported the biosynthesis and characterization of SNPs and AuNPs. The SNPs when compared to AuNPs, showed the highest antibacterial activity against Gram-positive and Gram-negative bacteria. Conclusion: The present study envisions on the biosynthesis of SNPs from T. divaricata plant which are emerging as antibacterial therapy in modern medical applications. Keywords: Antibacterial activity, Gold nanoparticles, Silver nanoparticles, Tabernaemontana divaricata.